Hubungan Antara Motivasi dengan Pengetahuan Tentang ASI Ekslusif - Suhaid, Dewi Novitasari (Ikatan Bidan Indonesia (IBI), 2024)
Breast milk is recognized as the optimal nutrition for infants aged 0 to 6 months. It is rich in essential nutrients necessary for the healthy growth and development of babies. Research has demonstrated that exclusive breastfeeding during the initial six months of life significantly enhances infant health, lowers the risk of infant mortality, and benefits maternal health as well. Nevertheless, a considerable number of mothers in Indonesia do not practice exclusive breastfeeding. According to the 2023 Indonesian Health Survey, only 68.6% of infants aged 0 to 5 months were exclusively breastfed. This situation can be attributed to various factors, including a lack of motivation and insufficient knowledge among mothers regarding exclusive breastfeeding. Motivation plays a crucial role in influencing behavior, and a strong desire to exclusively breastfeed can empower mothers to persist in this practice despite facing challenges. Additionally, understanding the advantages of exclusive breastfeeding can further bolster a mother's motivation to provide this essential nutrition to her child. This study seeks to examine the correlation between motivation and knowledge about exclusive breastfeeding. This study is an observational, analytical, cross-sectional study. The sample consisted of 58 mothers with toddlers aged 6 to 18 months. Data will be analyzed using Kendall's Tau test. The results demonstrated a mutually reinforcing connection between motivation and knowledge. This finding can serve as a strategic framework for promoting exclusive breastfeeding by utilizing various media for information dissemination, increasing motivation, and addressing breastfeeding challenges.